Changes in Cerebral Blood Flow with Age in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Changes in regional cerebral blood flow (rCBF) with age were studied by SPECT in 29 drug-naive patients with attention deficit hyperactivity disorder (ADHD) (24 boys, 5 girls; age 7-13) and 12 with complex partial epilepsy as controls, at NIMH International Mental Health Program, Istanbul; and University of Ankara Medical School, Ankara, Turkey.